Correction: An oral recombinant vaccine in dogs against Echinococcus granulosus, the causative agent of human hydatid disease: A pilot study. - PLOS Neglected Tropical Diseases Editors (PLoS Neglected Tropical Diseases, 2025)
[This corrects the article DOI: 10.1371/journal.pntd.0000125.].